Laura Kephart’s Letter to Leonard Kephart, May 18, 1933 - Upton, Jordan (2019)
This manuscript is a letter written from Laura Kephart, wife of writer Horace Kephart, to one of their sons, Leonard Wheeler Kephart. In the letter dated May 18th, 1933, only one year after the death of Horace in an automobile accident, Laura asks Leonard to check on copyright information on two of Horace’s books, Camping and Woodcraft and Our Southern Highlanders, and she proposes the addition of a new chapter to each. After this brief business formality, Laura begins to discuss familial matters and give general updates to Leonard on the rest of the family. Leonard’s brother, George, is working up north, presumably as a forester in Maine. Laura offers details on the Moores, Henry and Cornelia, one of Leonard’s sisters; Roy, married to another of Leonard’s sisters, Barbara; and Margaret, yet another sister. Laura then offers her sharp political opinions on recently elected President Franklin D. Roosevelt. She concludes the letter by writing about an unknown “Phil”, and finally, offering an update on the Fernows, Karl and Lucy, Lucy being the last Kephart child mentioned. An interesting note on the Fernows is that Karl and Lucy were in Germany at the time. Karl was on sabbatical from his professor position at Cornell University to travel overseas to study agricultural diseases, mainly in potatoes. While there, Karl’s laboratory host, Dr. Ernst Schaffnit, was arrested due to unknown circumstances, but perhaps related to the newly appointed Chancellor of Germany, Adolf Hitler, and his Nazi regime.